A Enhancing the physical and chemical characteristics of landfill leachate through a filtration system incorporating granite, iron filings, and recycled rubber waste - Balegh, Benamar; Sellaf, Hamid; Hadj Mostefa, Adda; Djafari, Driss; Meksi, Ali (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: The use of composite filters made from waste such as granite powder, iron filings, and rubber granules for treating landfill leachate is an innovative approach that can help mitigate the environmental impact of landfill sites. Methods: The experiment involved assessing the performance of single-layer and three-layer filters before and after treatment. To gauge the effectiveness of each filter configuration, the permeability coefficient is calculated for every cell. Calculating the permeability coefficient for single-layer and three-layer filters is an important aspect of assessing the efficiency of the treatment process for landfill leachate. It is also essential to consider other physical and chemical parameters (e.g. color, pH, oxidation coefficient, conductivity, BOD, COD, SS, NO4-, NO3-, NH4+, PO4-, and P) to assess the overall treatment efficiency and the removal of specific contaminants. Results: The results demonstrated a decrease in both physical and chemical factors with the formation of each cell. Notably, cell 5, consisting of a three-layer filter, exhibited favorable outcomes across physical and chemical parameters as well as permeability. Conversely, cell 2, containing granite powder, exhibited the best physical and chemical parameters but performed poorly in terms of the transmittance factor. Conclusion: These findings suggest that granite powder, iron filings, and rubber granules can serve as cost-effective filter layers for leachate treatment, helping alleviate its adverse environmental and groundwater impact.